2013
DOI: 10.1002/jor.22535
|View full text |Cite|
|
Sign up to set email alerts
|

Down‐regulation of collagen synthesis and matrix metalloproteinase expression in myofibroblasts from dupuytren nodule using adenovirus‐mediated relaxin gene therapy

Abstract: Dupuytren's disease is a fibroproliferative connective tissue disorder characterized by contracture of the palmer fascia of the hand. Relaxin (RLN) is a multifunctional factor which contributes to the remodeling of the pelvic ligament by inhibiting fibrosis and inflammatory activities. The aim of this study was to investigate the effect of the RLN gene on the inhibition of fibrosis in myofibroblastic cells. Myofibroblast cells with adenovirus LacZ (Ad-LacZ) as a marker gene or adenovirus relaxin (Ad-RLN) as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…207 Even though studies examining the effect of relaxin on collagen metabolism in human knee ligaments in situ are lacking, in vivo and in vitro animal studies and human cell culture studies suggest that relaxin administered at physiologic levels can have a profound effect on soft tissue remodeling. 204,[208][209][210][211] In turn, this may lead to a less organized 212 and less dense (both in fiber diameter and density) collagen structure, 204,212 which may manifest as a weaker and more lax ACL. 186 This concept is supported by an animal model in which guinea pig ACLs treated with relaxin at pregnancy levels were 13% more lax and 36% to 49% weaker.…”
Section: Hormonal Risk Factorsmentioning
confidence: 99%
“…207 Even though studies examining the effect of relaxin on collagen metabolism in human knee ligaments in situ are lacking, in vivo and in vitro animal studies and human cell culture studies suggest that relaxin administered at physiologic levels can have a profound effect on soft tissue remodeling. 204,[208][209][210][211] In turn, this may lead to a less organized 212 and less dense (both in fiber diameter and density) collagen structure, 204,212 which may manifest as a weaker and more lax ACL. 186 This concept is supported by an animal model in which guinea pig ACLs treated with relaxin at pregnancy levels were 13% more lax and 36% to 49% weaker.…”
Section: Hormonal Risk Factorsmentioning
confidence: 99%
“…Very recently, Kang et al reported the down‐regulation of collagen synthesis and matrix metalloproteinase expression in myofibroblasts from Dupuytren's nodule using adenovirus‐mediated relaxin gene therapy. Myofibroblastic cells with Ad‐RLN demonstrated a 22% and 48% reduction in collagen I and III mRNA expression, respectively, a 50% decrease in MMP‐1, 70% decrease in MMP‐2, 80% decrease in MMP‐9, and a 15% reduction in MMP‐13 protein expression compared with cultures with viral control and saline control . Dupuytren's contracture is characterized by excessive collagen deposition, which appears as cords causing an extension deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Myofibroblastic cells with Ad-RLN demonstrated a 22% and 48% reduction in collagen I and III mRNA expression, respectively, a 50% decrease in MMP-1, 70% decrease in MMP-2, 80% decrease in MMP-9, and a 15% reduction in MMP-13 protein expression compared with cultures with viral control and saline control. 24 Dupuytren's contracture is characterized by excessive collagen deposition, which appears as cords causing an extension deficit. In Dupuytren's contracture, there is an increase in the ratio of type III to type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Other substances have been postulated for DC treatment and they could be successful under these conditions. Among them, we note, especially, relaxin [36], IGF-II [37], anti-TNFα [38], or imiquimod [39]. Anti-TGFß would be the ideal candidate for the concomitant administration of this preparation.…”
Section: Discussionmentioning
confidence: 99%